Fire fighters and war work, 1942 (1942)
1942 1939-1945 "Fire fighters and war work, 1942" [HFR0214], 1942 The Fire Brigades Union supported Productive Work Schemes which sent fire fighters on long and short term release to work in war factories and on the land. However, not all members accepted the policy and this issue of The Firefighter in July 1942 devotes its front page and editorial to persuading members, especially outside of London, to support the Schemes.